2021
DOI: 10.1002/ccr3.4503
|View full text |Cite
|
Sign up to set email alerts
|

Coombs‐negative hemolytic anemia in a male with COVID‐19

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…COVID-19 infection has been reported to cause hematologic abnormalities, including cases of Coombs-negative hemolytic anemia. 2,3 Our patient presented with a unique combination of Coombs-negative hemolytic anemia and thrombocytopenia. Initially, we considered a broad range of differential diagnoses, including autoimmune, neoplastic, primary hematologic, and infectious causes.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…COVID-19 infection has been reported to cause hematologic abnormalities, including cases of Coombs-negative hemolytic anemia. 2,3 Our patient presented with a unique combination of Coombs-negative hemolytic anemia and thrombocytopenia. Initially, we considered a broad range of differential diagnoses, including autoimmune, neoplastic, primary hematologic, and infectious causes.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that SARS-CoV-2 might interact with erythrocytes, leading to invasion and potential hemolysis. 3,4 This interaction could involve the CD147 spike protein, which facilitates binding to receptor cells and invasion. 8 However, further research is required to elucidate this mechanism and characterize it more comprehensively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pandemic of the coronavirus disease 2019 (COVID-19), numerous multi-organ complications have been encountered from this infection in the clinical setting [ 1 ]. Hematological complications including autoimmune hemolytic anemia, venous thromboembolism, and disseminated intravascular coagulopathy (DIC) have been previously reported [ 2 ]. However, Coombs-negative hemolytic anemia is extremely rare with only three cases being reported so far [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%